Penerapan Inovasi Teknologi Mesin Penggorengan Vakum dan Pelatihan Olahan Kripik Buah di Kelompok Usaha Bersama(Kub) Ayu di Kelurahan Kranjingan Kecamatan Sumbersari Kabupaten Jember - Hesti Herminingsih (Politeknik Negeri Jember, 2017)
The objective of Community Service Scheme Program for Community in KUB Ayu Kelurahan Kranjingan is to assist partner business groups in their efforts to improve partner productivity through the application of appropriate technology and business management training. Problems related to the production process faced by partners are 1) food frying is still done by traditional way, and 2) Partners difficulty in managing financial administration, management of raw material stock control, management of stock control of finished material. Motode in the manufacture of vacuum frying machine (Vacuum Frying Machine) begins with the process of planning, manufacturing, testing, and training the use of machinery for members of partners. The implementation method consists of 4 stages, the first coordination and socialization of the activity plan, the two identification and validation of partnerproblems, the three design, assembly, and field test of equipment and machinery according to the needs of partner technology, the four counseling and mentoring. The result of Community Science and Community Service program can realize the implementation of vacuum fryer machine with specification of raw material capacity 3 kg / process, LPG fuel with automatic temperature control, water circulation coolant, cooking oil volume: 35 liters, power requirement 900 watt, 180 dimension X 120 x 120 cm, with an oil heating temperature range of 80 0C to 87 0C. The frying time ranges from 90-120 minutes. Variations of chips raw materials include; Jackfruit, pineapple, with depreciation rates of 70%, 60% and 80%, respectively. Training of financial administration management skills, management of raw material stocks, management of finished material stock control has brought social and economic impact to KUB Ayu's partners.Â Keyword : Training of fruit chips, Vacuum Frying Machine, KUB Ayu.